The Implementation of a Complete Systematic Land Registration Program to Realize Legal Protection and Public Welfare - Nareswari Kencana; Liza Priandhini (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
Land registration is one of the government's efforts to overcome land problems in Indonesia. One of the government's programs in an effort to maximize land registration in Indonesia is through a complete systematic land registration (PTSL) program/policy to ensure legal certainty and protection in order to create prosperity in the land sector for the community. Therefore this study aims to examine the problems that often occur in the implementation of PTSL in South Tangerang City and provide input regarding the concept of law enforcement for the implementation of PTSL so that it can run optimally. This research is an empirical juridical research with a form of diagnostic and descriptive research using two data collection tools, namely the study of documents or library materials, and interviews with South Tangerang City ATR/BPN officials and the community. The results of the study show that there are many problems in the implementation of PTSL in South Tangerang City caused by the not yet optimal Legal Structure and Legal Culture besides that there are also many technical obstacles. Second, the enforcement efforts that can be carried out are improvements in legal structure and legal culture, including increasing the number of PTSL officers and providing massive education to the public about the importance of land registration and the legal consequences received when committing fraud in land registration.